Baseline glucocorticoids are drivers of body mass gain in a diving seabird. Issue 6 (16th February 2016) - Hennin, Holly L.; Wells‐Berlin, Alicia M.; Love, Oliver P.
Abstract: Life‐history trade‐offs are influenced by variation in individual state, with individuals in better condition often completing life‐history stages with greater success. Although resource accrual significantly impacts key life‐history decisions such as the timing of reproduction, little is known about the underlying mechanisms driving resource accumulation. Baseline corticosterone (CORT, the primary avian glucocorticoid) mediates daily and seasonal energetics, responds to changes in food availability, and has been linked to foraging behavior, making it a strong potential driver of individual variation in resource accrual and deposition. Working with a captive colony of white‐winged scoters ( Melanitta fusca deglandi ), we aimed to causally determine whether variation in baseline CORT drives individual body mass gains mediated through fattening rate (plasma triglycerides corrected for body mass). We implanted individuals with each of three treatment pellets to elevate CORT within a baseline range in a randomized order: control, low dose of CORT, high dose of CORT, then blood sampled and recorded body mass over a two‐week period to track changes in baseline CORT, body mass, and fattening rates. The high CORT treatment significantly elevated levels of plasma hormone for a short period of time within the biologically relevant, baseline range for this species, but importantly did not inhibit the function of the HPA (hypothalamic–pituitary–adrenal) axis. Furthermore, an elevation in baseline CORT resulted in a consistent increase in body mass throughout the trial period compared to controls. This is some of the first empirical evidence demonstrating that elevations of baseline CORT within a biologically relevant range have a causal, direct, and positive influence on changes in body mass. Abstract : We elevated corticosterone within a biologically relevant, baseline range and found continual increases in body mass over time without negatively impacting HPA axis activity in a diving seabird. This is one of the first studies to demonstrate a positive, causal role of elevated baseline glucocorticoids mediating positive changes in an individual's condition or state. Our results therefore suggest that variation in baseline glucocorticoids may play a key role in mediating life‐history decisions and trade‐offs.